Who did what to whom? The neural basis of argument hierarchies during language comprehension - Bornkessel, Ina; Zysset, Stefan; Friederici, Angela D.; von Cramon, D. Yves; Schlesewsky, Matthias (NeuroImage (Orlando, Fla.), 2005)
The present fMRI study aimed at identifying neural correlates of the syntax–semantics interface in language comprehension. This was achieved by examining what we refer to as “argument hierarchy construction”, i.e., determining which participant in a sentence is the “Actor” and which is the “Undergoer” of the event expressed by the verb. In order to identify the neural bases of argument hierarchy processing, we manipulated three factors known to influence the complexity of argument hierarchy construction in German, namely argument order, verb class and morphological ambiguity. Increased argument hierarchization demands engendered enhanced activation in a network of inferior frontal, posterior superior temporal, premotor and parietal areas. Moreover, components of this network were differentially modulated by the individual factors. In particular, the left posterior superior temporal sulcus showed an enhanced sensitivity for morphological information and the syntactic realization of the verb-based argument hierarchy, while the activation of the left inferior frontal gyrus (pars opercularis) corresponded to linearization demands and was independent of morphological information. We therefore argue that, for German, posterior superior temporal and inferior frontal regions engage in the extraction of actorhood from morphosyntactic structure and in the sequential realization of hierarchical interpretive dependencies, respectively.